Are you drunk? No, I am CybAR sick! – interacting with the real world via pass-through augmented reality is a sobering discovery - Szentirmai, Attila Bekkvik; Alsos, Ole Andreas; Torkildsby, Anne Britt; Inal, Yavuz (Frontiers in Virtual Reality, 2025)
IntroductionThe recent paradigm shift in Augmented Reality (AR) technology features the integration of Pass-Through Augmented Reality (PT-AR) into flagship Extended Reality (XR) devices. PT-AR, from a technological standpoint is Virtual Reality (VR) and significantly differs from AR technologies that used in devices like Google Glass, Magic Leap, or HoloLens, which utilize Optical-See-Through AR. PT-AR renders the user’s physical environment on digital displays, as opposed to providing a direct, natural view of the physical world. This “virtual” digital representation of reality is an unexplored area. What makes AR distinct from other technologies, including VR, is its “reality” aspect. AR overlays, projects, and enhances the user’s physical environment with digital information. Accordingly, the primary scene of interaction in AR is the real world. This study takes a novel approach by focusing on the “reality” aspect of AR. It compares two commercially available PT-AR systems: a low-end smartphone-based device and a high-end dedicated headset. The study examines how each affects users’ comfort, orientation, and task performance during everyday activities in the physical world.MethodsWe employed a mixed-method approach, involving 20 participants with diverse backgrounds in terms of age, gender, and VR/AR experience. We evaluated the impact of PT-AR across three foundational real-world task domains, such as walking, dexterity, and full-body coordination, via NASA Task Load Index (NASA-TLX) and Simulator Sickness Questionnaire (SSQ) assessments, observations, and interviews.ResultsOur findings suggest that current PT-AR solutions negatively affect user comfort, orientation, wellbeing, and task performance. Both systems fall short of AR’s promise of seamless engagement and integration of reality. Participants exhibited symptoms similar to those of intoxication, including loss of body coordination, general discomfort, and difficulties in focusing and concentrating.DiscussionWe argue that PT-AR may introduce a new form of discomfort that differs from well-known issues like cybersickness or motion sickness, which require further research on XR’s “reality” aspects to understand the interaction between human and technological factors comprehensively.